GE_GERICHTE P/11288/2019 vom 12. Juni 2019 - GE Cour de justice (2019)
CLASSEMENT DE LA PROCÉDURE;DIFFAMATION;MORT;LIVRE;LIEU DE COMMISSION;LIEU DE RÉSULTAT | CPP.310.al1.letb; CP.8.al1; CP.173; CP.175.al1